(untitled) (Między Oryginałem a Przekładem, 2024)
THE FIRST POLISH TRANSLATION OF CAMÕES’ LUSIADS This year we celebrate the 500th anniversary of the birth of Luis de Camões, Portugal’s greatest poet. For a translation scholar, this is a special occasion to mention the first Polish translation of The Lusiads, published in 1790 by the unjustly forgotten, or rather: unjustly disregarded by posterity, Prof. Jacek Idzi Przybylski. This article aims to recall the achievements of the Kraków classical philologist, a translator of Voltaire’s most important works, but also of Homer’s Iliad, Virgil’s Aeneid and Georgics, Milton’s Paradise Lost, the works of Ovid, Horace, Hesiod… Przybylski’s work is uneven, but the mockery of his contemporaries, including the Enlightenment arbiter of elegance Dmochowski, was provoked by his predilection for creating not always fortunate neologisms – let us add, mainly in scientific works, to a much lesser extent literary ones. Dmochowski had personal reasons for his dislike of Przybylski, but this was not noticed by his contemporaries -– and surprisingly, once a malicious assessment was popularized, it was thoughtlessly repeated until the end of the 1970s. The analysis of the literary merits of Przybylski’s Luzyada, carried out by the author of this article, indicates, however, that the aforementioned negative judgments were extremely hasty. According to the author, this translation is worth restoring to the readership, for several reasons. First, none of the later translations impress us, and it is difficult to expect that someone in modern times will make another, more successful attempt. Second, when translating old poetry, we have a choice between the Scylla of archaic stylization and the Charybdis of modern translation. Przybylski’s 18th-century translation fortunately avoids both dangerous reefs: its antiquity is natural, so it already constitutes a certain added value at the starting point. What is more, however, the best fragments of this translation surprise us to this day with their freshness and originality.